THE ROLE OF COMPUTER AND INFORMATION TECHNOLOGY SCIENCE IN DEVELOPED FOREIGN COUNTRIES (Web of Discoveries: Journal of Analysis and Inventions, 2024)
In this article, the history of computer science in foreign countries, teaching experience, its useful aspects, opportunities and advantages of teaching methods for students of informatics and information technologies are widely covered.